Hubungan antara Pola Menstruasi dengan Kejadian Anemia pada Mahasiswi Prodi Sarjana Kebidanan Unissula Semarang - Suhariyati Suhariyati; Alfiah Rahmawati; Friska Realita (Jurnal Akademika Baiturrahim Jambi, 2020)
Anemia is a health problem for people around the world, especially in developing countries. Teenagers have a high risk of anemia, especially iron anemia. That happens because adolescence requires higher nutrients including iron for growth and development. Young women have a higher risk than young men, this is because young women experience menstruation every month (menstruation). The purpose of this study was to determine the relationship between menstrual patterns and the incidence of anemia in young women in Unissula Midwifery Study Program in Semarang. Method: This study used an analytical survey method with a cross sectional study design. The study was conducted in May with a sample of 39 female students of the second semester of unissula midwifery study program. The sampling technique used is total sampling. Menstrual pattern data were obtained through a structured questionnaire, and hemoglobin levels were obtained by examination using the Family DR tool. Data collection includes coding, editing and tabulating, then the data are analyzed with Chi square. The results showed the relationship of menstrual patterns with the incidence of anemia in young women in Unissula Semarang Midwifery Study Program, it was found that the p value <0.05 (0,000). Conclusion: It can be concluded that there is a significant relationship between menstrual patterns and the incidence of anemia in adolescents in Unissula Midwifery Bachelor Study in Semarang. Adolescents are expected to increase knowledge about anemia and can change adolescent eating behavior for the better